Os meninos e as fábricas: a incorporação do social na literatura alegórica de José J. Veiga - João Pedro de Carvalho (2022)
This dissertation mobilizes the literary production of José J. Veiga (1915-1999), author of literature from Goiás, Brazil, to investigate the modernization processes that took place throughout the 20th century in the Brazilian hinterlands. In the first part of the work, we discuss the authoritarian way in which transformations in this region were proposed, especially during the Civil-Military Dictatorship of 1964, and the artifices used by Veiga to signify these processes, such as the use of Unheimlich and the allegorical form of the speech. In a second moment, we investigate historical traumas in the Brazilian context related to the imposition of new productive modes and the ways in which literature, in different works by Veiga and even by other writers, acted to express the sensitivity of subjects impacted by the change in a culture. Finally, in the third chapter of the dissertation, we observe the (non) formation of children's characters by the author and interpret how the feelings of melancholy and anguish, as well as the absence of experiences characteristic of capitalist modernity relate to the problems of material and cultural transformation incorporated in different works by José J. Veiga.